Integration of Virtual Reality Media in Teaching Factory to Enhance 4C Skills in Vocational Education - Primartadi, Aci; Jatmoko, Dwi; bin Kamin, Yusri; Arifin, Zainal (IJORER : International Journal of Recent Educational Research, 2025)
This study aims to explore the integration of Virtual Reality (VR) technology into automotive learning based on Teaching Factory to support the development of 21st century competencies Critical Thinking, Creativity, Collaboration, and Communication (4C) in vocational high school students. A descriptive qualitative approach was used, with data collected through interviews, observations, literature reviews, and documentation analysis of teachers and students in the field of light vehicle engineering. In addition, a survey was conducted in several vocational high schools to complement the findings. The results indicate that the use of Virtual Reality enhances students’ creativity and critical thinking, improves their understanding of industrial work procedures, and provides a realistic and safe learning environment. This study contributes to research on digital learning tools in vocational education by highlighting the potential of integrating Virtual Reality in a Teaching Factory setting, which is still underexplored in current practice.